PROMOTION EFFECT ANALYSIS ON THE SALES VOLUME OF HONDA MOTORCYCLE AT PT TIMBUL MANDIRI JAYA BOYOLALI - A.FIDHIARR ARIESTANTO TNK; UNNA RIA SAFITRI; ADINDA RYAN MARGANTIKA (CV KULTURA DIGITAL MEDIA, 2021)
This study aims to determine the effect of promotion on the sales volume of Honda motorcycles at PT Timbul Mandiri Jaya Boyolali. Methods of data collection using questionnaire method. The data analysis used is multiple regression analysis and significance testing using the t and f test. The result show that that there is a positive and significant effect of advertising, personal selling and direct marketing to sales volume with < with significance of 5% or 0,05, while the remaining 2 variables are sales promotion and public elations which have no positive and insignificant effect on sales volume.